Edukasi Jenis Makanan Berbasis Bukti Cegah Kanker di Kelurahan Tomang Kecamatan Grogol Petamburan Jakarta Barat - Ribka Panjaitan; Astrid Komala Dewi; Sarah Geltri Harahap; Fransiska Suryasari; Ludovikus Ludovikus; Dewi Nuryani; Hildegardis Yolenta (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
Community Service Activities are one of the essential obligations that must be carried out by academic programs as part of implementing the Tri Dharma of Higher Education. PkM serves as a platform for lecturers to contribute meaningfully to improving community well-being. This activity aimed to provide education on evidence-based food types for cancer prevention to the residents of RT 08 RW 07, Tomang Subdistrict, Grogol Petamburan District, West Jakarta. The program was implemented through lectures, interactive discussions, and healthy menu simulations, supported by educational leaflets. The materials covered an overview of cancer, the role of nutrition in cancer prevention, recommended and avoidable foods, and practical tips on reading nutrition labels. Evaluation was conducted using pre-tests and post-tests to measure participants’ knowledge improvement. The results showed a significant increase in knowledge with an average N-Gain score of 67%, categorized as moderately effective. Furthermore, participants’ active engagement during discussions and simulations indicated high interest in the information delivered. This program demonstrates that evidence-based nutrition education, when communicated contextually and interactively, can serve as an effective promotive and preventive strategy in reducing cancer risk within the community.